KEPEMIMPINAN PROFETIK KEPALA SEKOLAH DAN BUDAYA SEKOLAH DALAM PEMBENTUKAN KARAKTER SISWA DI MTSS PLUS FASTABIQUL KHAIRAT SOLOK SELATAN - Fauzi Fauzi; Nunu Burhanuddin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the prophetic leadership model of the madrasah principal, the process of internalization and implementation of prophetic leadership in shaping students’ character, as well as the supporting and inhibiting factors in its application at MTsS Plus Fastaqul Khairat. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation involving the principal, vice principals, teachers, and students. The findings show that the principal’s leadership is a transformational-prophetic model that integrates Islamic values with modern educational management. The prophetic values applied include siddiq (honesty), amanah (responsibility), tabligh (communication), and fathonah (wisdom), which are internalized through exemplary behavior, habituation, and school culture. The implementation of these values is reflected in daily activities such as morning religious talks, congregational prayers, transparency in management, and the habituation of honest and disciplined behavior. As a result, students’ character is formed as religious, disciplined, honest, responsible, and polite. The main supporting factors are leadership exemplarity, a religious school culture, and the support of school members, while the inhibiting factors include external environmental influences, social media, and differences in students’ backgrounds. Overall, prophetic leadership has been proven effective in building school culture and shaping students’ character.